Takhayyur application in muamalat practices / Nur Farzana Mohd Nurji. - Mohd Nurji, Nur Farzana (2019)
As the economic development has increasingly developing in line with the technological advances nowadays across the world, especially in transactions where there is an issue that could lead to the combination of activities or practices of scholars includes Hanafi, Maliki, Syafi’i and Hanbali in a community or society. Predominantly, the application of products in the Islamic banking and finance must be line with the views of Syafi’i school. As the consequence of that, Muslim in Malaysia refused to combine other different schools to be applied in transaction as to avoid from disputation and contradiction of opinion between those schools. Thus, this study attempts to illuminate the issues by addressing the scope muamalat practices and implementation in selection of schools view. This also will focuses on takhayyur application as innovative tools based on Shariah principle will be discussed with a special approach on muamalat in Malaysia. This study will support with prominent Muslim scholars’ views on takhayyur and also analyzed the relevancy of applied in the mualamat practices globally. This study adopts qualitative study research methodology whereby descriptive and explanatory approaches were used. This study believed that takhayyur approach could serve as a benchmark to constitute a sufficient measure to address the issues properly.